The Relationship between Corporate Philanthropy and Firm Market Value, and the Extent to Which the Level of Financial Slack Resources Affects this Relationship - ALQuran, Heba Ahmad; Alshorman, Salah Aldain Abdullah (Jordan Journal of Business Administration, 2025)
This study examines the relationship between corporate philanthropy and firm market value and the extent to which this relationship is affected by the level of financial slack resources. The sample of the study consists of (462) observations representing (58) industrial and service companies listed in the Amman Stock Exchange (ASE) during the period (2010-2019). Corporate philanthropy is measured by the total cash donations as stated in the Board of Directors’ report, and financial slack resources are computed using the ratio of current assets to current liabilities. The theories of stakeholders, legitimacy, and slack resources explain the relationship between financial slack resources, corporate philanthropy, and firm market value. A fixed-effect egression model is used to test the hypotheses of the study. The study's findings show a positive, but insignificant, relationship between corporate philanthropy and firm market value and that financial slack resources moderate this relationship. Specifically, it is found that sufficient financial resources positively moderate the relationship between corporate philanthropy and firm market value, while this relationship becomes negative when financial resources are limited. Therefore, this study concludes that financial slack resources represent an important factor in explaining when corporate philanthropy has value in the financial market in the Jordanian context.